Energy absorption characteristics of functionally graded polymer-based lattice structures filled aluminum tubes under transverse impact loading. (1st November 2021) - Nian, Yuze; Wan, Shui; Zhou, Peng; Wang, Xiao; Santiago, Robert; Li, Mo
Graphical abstract: Highlights: Functionally graded lattice-filled circular tube (FGLCT) fabricated by 3D printing technology is reported. FGLCT exhibit 173.9% increase in specific energy absorption and 74.9% in peak crushing force. The radial graded pattern of FGLCT is more conducive to improving energy absorption to axial graded pattern. The effective filling length approach can reduce structural self-weight while ensuring high energy absorption. Abstract: This paper aims to evaluate the potential use of an innovative functionally graded lattice-filled composite beam composed of axial and radial graded three-dimensional lattice cores. Graded lattice filled circular beams with different graded patterns are compared with homogenous lattice filled counterparts. Graded lattice core samples are prepared using 3D printing techniques, inserted into thin-walled tubes and subjected to three-point bending loads. Then numerical models are created in Abaqus and verified against the experiments. Parametric studies find that the novel lattice-filled structure absorbs more energy but yields larger crushing force than the uniform counterpart. In addition, various parameters, like gradient parameter and filling length, thickness and yield stress of column wall, have a considerable impact on the crashworthiness of this novel structure. Finally, multi-objective optimization is performed to maximize specific energy absorption while reducing maximum impact force. Optimization results show that graded lattice-filled structures produce superior Pareto solutions than the ordinary counterparts. Especially, the specific energy absorption can be increased to 173.9% and increasing graded lattice-filled structure has the best crashworthiness, and the least decreasing graded lattice-filled structure. The functionally graded lattice core of this study provides a novel approach to design new crash-resistant energy absorber with high energy absorption capacity.